Carbonic anhydrase inhibitors limit complications in X-linked retinoschisis - Stephanie Wey; Stephanie Wey; Stephanie Wey; Daniel A. Brill; Daniel A. Brill; Daniel A. Brill; Virginia Miraldi Utz; Virginia Miraldi Utz; Robert A. Sisk; Robert A. Sisk; Robert A. Sisk (Frontiers in Medicine, 2023)
PurposeCarbonic anhydrase inhibitors (CAIs) reduce macular schisis in patients with X-linked retinoschisis (XLRS). The purpose of this study was to determine if CAIs reduce the incidence of complications from XLRS, including macular atrophy, retinal tears, and retinal detachment (RD), the most common causes of vision loss in patients with XLRS.MethodsFor this retrospective interventional case series, a chart review of patients examined at Cincinnati Children’s Hospital Medical Center [CCHMC] and Cincinnati Eye Institute [CEI] between 1/1/2015 and 1/16/2023 was performed. Male patients were included based on genetically-confirmed RS1 or typical clinical presentation with known family history of XLRS with at least two follow-up visits.ResultsTwenty-eight patients (56 eyes) with XLRS were included. There were 10 RS1 variants among the 21 genotyped patients. Median age at clinical diagnosis was 10.4 years old (range: 0.4–55.7 years) with median follow-up time of 4.7 years (range: 0.2–38.3 years). Median presenting Snellen visual acuity was 20/60 (logMAR 0.48, range: 0.18–3). In 26 eyes of 15 patients treated with CAIs, median CST pre-treatment was 416 microns (range: 198–701 microns), and median percentage decrease in CST on treatment was 21.8% (range: 0–74.5%) from highest pre-treatment CST. Reduction in CST with CAI use was statistically significant (p = 0.02), but not logMAR VA (p = 0.64). There was no significant difference in CST between patients treated with topical vs. oral CAI (p = 0.95) or between patients with partial or complete CAI adherence (p = 0.60). Ten eyes of seven patients had an RD requiring surgical intervention. No treated eyes developed new macular atrophy, peripheral retinoschisis, retinal tears, or RD; two eyes on topical CAIs had spontaneous resolution of bullous peripheral retinoschisis.ConclusionDuring the follow-up period, patients taking CAIs reduced macular schisis and did not experience new complications of macular atrophy, retinal tears, or RD. This is a relatively large cohort with long-term follow-up periods for patients with XLRS. Reduced macular schisis may not require perfect adherence with CAIs. A large, prospective, randomized, controlled clinical trial is needed to determine the potential of CAIs to improve visual function, reduce retinoschisis, and prevent RD.